Cultural Politics of Indis in Yogyakarta Palace in a Photography Study - Widyo Harsanto, Prayanto; Farid Sagir, Rudy (International Journal of Psychosocial Rehabilitation, 2020)
This study discusses the role of photography as a work of documentation that records events and situations in Yogyakarta Palace during the Dutch colonial era in Indonesia. Because at Keraton Yogyakarta has a role in the development of Indis culture, both social and cultural traditions/customs, which causes the meeting of two strengths, namely colonial and traditional powers. This study aims to visually read Indis’ cultural phenomena as well as uncover the meaning behind the image of the photograph. The visual approach was used as a method in this study through Walter Benjamin’s concept of’Photography is politic ’, while the way Gillian Rose and Weber made’visual-based ’approach’The’ author’s footing to read and analyze photographic works in the Dutch East Indies era. Through visual documentation can be revealed and explained that for the people of Indis, photography is not merely a technology and art product, but it is full of human-created symbols and used to interpret his life. In this case, photography is made possible as a political medium to reveal ideas and is one of the efforts to influence the thinking and behaviour of one person, society, and institution/ruler. This photography study depicts’Victorian ’Orientalis’through’ photo images (particularly portraits/human subjects) with a rigid pose appearance, tense face, and serious to illustrate dignity, politeness, success, and show a person’s cial status. Similarly, the theme of two nations, the Netherlands and Java/Yogyakarta, can form the historical construction of Western culture and eastern culture.